ViVoVAD: a Voice Activity Detection Tool based on Recurrent Neural Networks - Gimeno Jordán, Pablo; Bailo, Ignacio Viñals; Giménez, Alfonso Ortega; Artiaga, Antonio Miguel; Solano, Eduardo Lleida (Jornada de Jóvenes Investigadores del I3A, 2019)
Voice Activity Detection (VAD) aims to distinguish correctly those audio segments containing human speech. In this paper we present our latest approach to the VAD task that relies on the modelling capabilities of Bidirectional Long Short Term Memory (BLSTM) layers to classify every frame in an audio signal as speech or non-speech